The Ability of PAUD Teacher Education Students to Develop a Cheese Roll Culinary Business to Increase the Entrepreneurial Spirit in the 4.0 Revolution Era - Sari, Octarina Mayang; Yuliandari, Izzazur Rohmah (CV Media Inti Teknologi, 2023)
Entrepreneurship is a mental attitude and spirit that is always active, creative, inventive, initiative and modest in trying to increase income in business activities. Someone who has an entrepreneurial spirit and attitude always feels dissatisfied with what he has achieved. Business is one of the main activities in supporting economic development. Here we take the culinary business